THE COMMON GOOD AND CHRISTIAN ETHICS (Hekima Review, 2024)
David Hollenbach, SJ, hardly needs introduction to students and scholars of Christian Social Ethics, since he has been publishing right from 1979. The principle of the common good, which is a major focus of his study, is not new. What is new however, is the application of this age-old principle to contemporary issues, namely: urban poverty and globalization which is marked by unequal interdependence.